1999
DOI: 10.1007/bf02433836
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular reorganization and ultrastructural stereological analysis of cardiomyocytes of W/SSM rats with genetically determined cardiomyopathy

Abstract: We studied ultrastructure of cardiomyocytes of W/SSM rats with inherited hypertrophic cardiomyopathy bred from Wistar rats by hypersensitivity to cataractogenic action of high galactose doses. The observed dynamics of quantitative and qualitative changes in the main sarcoplasmic organelles reflects general principles of spatial and temporal reorganization of cardiac muscle cells induced by hypertrophy of different genesis.Key Words: W/SSM rats; hypertrophic cardiomyopathy; cardiomyocytes; electron microscopy; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Among these latter ones are SAM mice (more than 10 substrains are known) [11][12][13] and OXYS rats, bred in Russia, which are characterized by genetically determined metabolic defects [9]. Recent studies revealed shortening (by 28%) of the maximum life span in these animals, high incidence of "diseases of elderly age", early emergence of involution changes in the viscera, and cognitive deviations [1,[4][5][6][7][8].Study of the compensatory adaptive reactions and spatial reorganization of the adrenals is important, as adequate functioning of the adrenals maintains the regulation and interactions of many systems responsible for vital activity [10]. Despite the significance of age-specific reorganization of the adrenals and their individual structural and functional compartments, this aspect remains little studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these latter ones are SAM mice (more than 10 substrains are known) [11][12][13] and OXYS rats, bred in Russia, which are characterized by genetically determined metabolic defects [9]. Recent studies revealed shortening (by 28%) of the maximum life span in these animals, high incidence of "diseases of elderly age", early emergence of involution changes in the viscera, and cognitive deviations [1,[4][5][6][7][8].Study of the compensatory adaptive reactions and spatial reorganization of the adrenals is important, as adequate functioning of the adrenals maintains the regulation and interactions of many systems responsible for vital activity [10]. Despite the significance of age-specific reorganization of the adrenals and their individual structural and functional compartments, this aspect remains little studied.…”
mentioning
confidence: 99%
“…Among these latter ones are SAM mice (more than 10 substrains are known) [11][12][13] and OXYS rats, bred in Russia, which are characterized by genetically determined metabolic defects [9]. Recent studies revealed shortening (by 28%) of the maximum life span in these animals, high incidence of "diseases of elderly age", early emergence of involution changes in the viscera, and cognitive deviations [1,[4][5][6][7][8].…”
mentioning
confidence: 99%